Assigning responsibility for a structural failure. (April 2016) - Le May, E.; Le May, I.
Highlights: A method which may be used to assign responsibility for a structural failure. Intended to be used by non-engineers who need to grasp technical issues. Potentially useful where a number of parties are involved in a failure. Abstract: Fault Tree Analysis (FTA) is typically used during the engineering design process to plan for the avoidance of in-service failure. This paper presents a variation of FTA; this has been adapted to assist non-engineers with the identification of the causes of structural failures and to indicate the relationship between these causes and the party or parties who should accept responsibility for them. Examples are provided to illustrate the methodology and its application.